Gas Lift Optimization using Numerical Method - BRAMANA (NIM 12205030); Pembimbing: Dr. Ir. Pudjo Sukarno, SATRIA
Gas lift is an artificial lift operation designed to assist the production of an oil well by injecting gas at certain rate. Gas lift design consist of designing optimum gas injection rate, which usually done by constructing a Gas Lift Performance Curve (GLPC) to acquire the Gas Liquid Ratio (GLR) that generates the optimum oil rate (q). Nodal system analysis is a method to determine optimum q at one nodal point which acquired from the intersection of IPR and TPR curve. The TPR curve is affected by the GLR value, it means that various GLR value will generate various q needed to construct the GLPC. In this paper the solving of nodal system analysis will be done numerically by substituting the TPR equation into the IPR equation to obtain the q at intersection of those two curves formed by those two equations. A new software will be developed to calculate the optimum q then to construct the GLPC, where the generated optimum q will be validated using similiar existing software.